2019
DOI: 10.1038/s41598-018-36758-6
|View full text |Cite
|
Sign up to set email alerts
|

Birth weight percentiles by sex and gestational age for twins born in southern China

Abstract: Mean birth weight of twins is known to be lower than that of singletons, however, southern China lacks a twin-specific birth weight reference. In this paper, we use data from the Birth Certificate System in southern China, collected between January 1st 2014 and December 31st 2017 and including 161,076 twins, to calculate sex- and gestational week-specific birth weight percentiles (the 3rd, 10th, 25th, 50th, 75th, 90th, and 97th). We applied generalized additive models for location, scale and shape (GAMLSS) whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The prevalence of SGA twins depends on the definition used. Due to the lack of reference, growth standards for singletons are commonly used to assess twin growth in clinical practice [ 23 , 33 ]. Previous studies showed that the growth trajectory of twins diverges from the one of singletons in the third trimester [ 13 , 19 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of SGA twins depends on the definition used. Due to the lack of reference, growth standards for singletons are commonly used to assess twin growth in clinical practice [ 23 , 33 ]. Previous studies showed that the growth trajectory of twins diverges from the one of singletons in the third trimester [ 13 , 19 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite several birth weight standards for twin gestations has been published in recent years in China [ 15 , 33 , 38 ], these standards seem not promoted. We undertook a local validation to assess the appropriateness of the chosen standards.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional values of low birth weight (2,500 gm) are determined by uterine growth expressed as the gestational age-specific birth-weight percentile. 9 Preterm birth (less than 37 weeks of gestation). 10 All of the children in the sample had physical exams, medical records reviewed, and tests performed in the lab, including measurements of arterial blood gas, serum hemoglobin, and chest X-rays to rule out diseases not identified during clinical evaluation.…”
Section: Methodsmentioning
confidence: 99%